ACTUAL PROBLEMS OF OWNER'S EQUITY ACCOUNTING - Ermatov Akmaljon Akbaraliyevich (Web of Journals Publishing, 2024)
This article highlights the current problems of accounting for owner's equity in companies established on the basis of equity participation, issues that need to be taken into account in the context of the transition to the digital economy. In light of these examples, a number of problems that arise in the process of organizing and maintaining shareholders equity accounting today and their nature are revealed.
Keywords: owner's equity, financial reporting, digital economy, asset value, types of shares, shareholders equity structure, bonds, new financial instruments, digital assets, dividends.